ANALYSIS OF BIRTH, DEATH, AND MIGRATION IN KEDIRI CITY, EAST JAVA - Ken Rayi Naila Adni; Bejo Apriyanto; Sri Astutik; Fahrudi Ahwan Ikhsan (DEPARTMENT OF GEOGRAPHY EDUCATION, UNIVERSITY OF JEMBER, 2020)
Population growth is a dynamic of wages in a population from time to time. Population growth is influenced by several factors, including births, deaths, and migration. In demography itself, it is commonly referred to as natural population growth and total population growth. This article uses a quantitative research method with secondary data sources coming from BPS 2021 data. The data collection technique used is a literature study technique, and the data analysis technique uses formulas or quantitative calculations. In this paper can be found about fertility, mortality, and migration in the city of Kediri. Not only that, this paper also describes how fertility, mortality, and migration rates affect the rate of growth and population projections in Kediri City.